Quality-controlled dose-reduction of pelvic X-ray examinations in infants with hip dysplasia - Kloth, Jost; Neumann, Regina; Stillfried, Eva von; Stiller, Wolfram; Kauczor, Hans-Ulrich; Ewerbeck, Volker; Weber, Marc-André (European journal of radiology, 2016)
Background: Digital plain radiography (DR) examinations of the pelvis are frequently performed in infants with hip dysplasia. Objective: The purpose was to reduce the radiation dose and to determine objective quality control criteria to ensure accurate assessment. This seems feasible because of higher quantum efficiency of DR and easy assessable anatomical structures for most orthopaedic measurements. Materials and methods: Institutional review board approval was obtained. In this prospective randomized study, 264 patients underwent X-ray examination of the pelvis with standard and reduced dose. The evaluation of the plain-radiographs was conducted using the following criteria: acetabular and center edge angle, closing of the epiphyseal plates and maturation of the femoral head. Two radiologists evaluated these criteria using a score ranging from 1 (definitely assessable) to 4 (not assessable). If a single criterion had been evaluated with a score of 3 or more points or more than 2 criteria with 2 points, the radiograph was scored as “not assessable”. The statistical analysis was conducted as non-inferiority-trial. Results: Five (1.9%) examined X-rays were scored as not assessable. There was no statistical inferiority between the examinations with standard (4.57 μSv) or reduced dose (3.06 μSv). Also, the individual evaluation of the defined criteria was dose-independent. Conclusion: The adequate evaluation of hip dysplasia in children and young adults on pelvic radiographs is possible with reduced radiation dose, by simple using an exposure class of 800 instead of 400.
Online veröffentlicht: 23. November 2015
Gesehen am 07.04.2017